The Most Suitable Locations for the Establishment of Wind Farms on the Red Sea Cost in Saudi Arabia - Al Khalif, Jihan Abdulqader; Siam, Nader Mohammed (Journal of natural sciences, life and applied sciences, 2018)
In this study the characteristics of the prevailing winds in the four coastal cities located on the cost of the Red Sea (Wejh, Yenbo, Jeddah, Gizan) in Saudi Arabia were compared, as will as the characteristics of onshore and offshore wind, as for the direction and speed. The study used climatic data available from the General Presidency of Meteorology and Environment Protection in Saudi Arabia for the period between 1985- 2004 AD. Excel and SPSS computer programs for the data analysis.  The study showed that the average and maximum onshore wind were speeder than the offshore wind in all stations except for a few months in Jeddah and Gizan.Examined the possibility of producing electricity using Wind Turbines, It was found that wind speed in the Wejh was promising to produce electricity more than other stations in all months of the year, while in Yenbo in the summer months only.
Keywords: surface wind; prevailing wind; wind pressure; wind energy; wind farms